Incidental L2 vocabulary acquisition from and while reading - Pellicer-Sánchez, Ana (Cambridge University Press, 2016)
Previous studies have shown that reading is an important source of incidental L2 vocabulary acquisition. However, we still do not have a clear picture of what happens when readers encounter unknown words. Combining off-line (vocabulary tests) and online (eye-tracking) measures, the incidental acquisition of vocabulary knowledge from reading and the online reading of unknown lexical items were examined. L2 English learners read a story containing unknown items while their eye-movements were recorded. After eight exposures, L2 readers recognized the form and the meaning of 86% and 75% of the target nonwords respectively, while they recalled the meaning of 55% of the nonwords. After three-four encounters nonwords were read significantly faster and by eight encounters they were read in a similar manner to previously known real words. Results also showed a positive relationship between new vocabulary learning outcomes and online reading, with longer reading times associated with higher vocabulary recall test scores.The study was also conducted with L1 readers to provide baseline data for comparison. Results confirmed the L2 findings while also indicating an interesting L1-L2 distinction in the rate rather than in the ultimate outcome of the acquisition process.